Prevalence of metabolic syndrome in psoriasis vulgaris: a cross sectional study from a tertiary care hospital of South-East Rajasthan - Morgaonkar, Manjaree; Kushwaha, Ramesh; Gupta, Savera; Jain, Suresh Kumar; Kulkarni, Dattatray V.; Sharma, Chandra Prakash (International Journal of Research in Dermatology, 2016)
Background: Psoriasis, a common skin disorder is now considered as systemic inflammatory disease. Its chronic inflammatory state is thought to predispose patients to metabolic syndrome (MetS), which is a significant predictor of cardiovascular events. The objective of the study is to investigate the prevalence of metabolic syndrome in psoriatic patients with only cutaneous involvement and to evaluate the correlation between presence of MetS and psoriasis severity Methods: We performed hospital based, cross-sectional study on 100 adult patients with psoriasis vulgaris and equi-numbered age and sex matched controls. MetS was diagnosed by revised National Cholesterol Education Program’s Adult Panel III criteria. Results: A higher prevalence of metabolic syndrome was found in psoriasis patients as compared to controls [28 (28%) vs 9 (9%), P value=0.0005].Impaired fasting glucose level, hypertension, hypertriglyceridemia and abdominal obesity were more prevalent in psoriasis group. No statistically significant difference was found between prevalence of low levels of HDL and presence of metabolic syndrome. Presence of metabolic syndrome was not associated with severity and duration of psoriasis. Female patients with psoriasis were more frequently having metabolic syndrome. Conclusions: Prevalence of metabolic syndrome is higher in patients with psoriasis irrespective of its duration and severity. This stresses on the need of regular evaluation for the presence of MetS or any of its components in psoriasis patients so as to allow early detection and management.